Exome sequencing of extreme clopidogrel response phenotypes identifies B4GALT2 as a determinant of on‐treatment platelet reactivity. Issue 3 (20th June 2016) - Scott, SA; Collet, J‐P; Baber, U; Yang, Y; Peter, I; Linderman, M; Sload, J; Qiao, W; Kini, AS; Sharma, SK; Desnick, RJ; Fuster, V; et al.
Abstract : Interindividual variability in platelet aggregation is common among patients treated with clopidogrel and both high on‐treatment platelet reactivity (HTPR) and low on‐treatment platelet reactivity (LTPR) increase risks for adverse clinical outcomes. CYP2C19 influences clopidogrel response but only accounts for ∼12% of the variability in platelet reactivity. To identify novel variants implicated in on‐treatment platelet reactivity, patients with coronary artery disease (CAD) with extreme pharmacodynamic responses to clopidogrel and wild‐type CYP2C19 were subjected to exome sequencing. Candidate variants that clustered in the LTPR subgroup subsequently were genotyped across the discovery cohort ( n = 636). Importantly, carriers of B4GALT2 c.909C>T had lower on‐treatment P2Y12 reaction units (PRUs; P = 0.0077) and residual platelet aggregation ( P = 0.0008) compared with noncarriers, which remained significant after adjusting for CYP2C19 and other clinical variables in both the discovery ( P = 0.0298) and replication ( n = 160; PRU: P = 0.0001) cohorts. B4GALT2 is a platelet‐expressed galactosyltransferase, indicating that B4GALT2 c.909C>T may influence clopidogrel sensitivity through atypical cell‐surface glycoprotein processing and platelet adhesion.